ANALISIS RANTAI NILAI IKAN LELE DI KABUPATEN SLEMAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2015)
The objective of this research were to analyze value chain of catfish, relationship between catfish production and factor of production inputs and relationship between catfish farmers income and price of production inputs. The respondens are catfish farmer and wholesalers. The results indicates that critical factors that hamper catfish production and farmers income are capital, fry supply, fry quality, availabilityof water, water quality, feed, farm design, over production, fluctuation price.